PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN PADA (WARUNG NASI KUD) CIKARANG BARAT - Trisnawati Trisnawati; TS. Reza (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This researchaims to analyze the influence of price and product quality towards customers loyalty. It is heldand Warung Nasi KUD West Cikarang. Quantitative research method is used in this researh as the methodof the research, and multiple linear regression is used as the data analysis method. To analyze the data thisresearch uses SPSS 24.0 software for windows. The population of this research is the customers of WarungNasi KUD West Cikarang , while the sample, 60 people, is chosen by using Hair et al. method.The result ofthis research shows that the independent variables, price variable has positive and significant effect 23,4%toward the customers loyalty, product quality variable has positive and significant 52,1% towards thecustomers loyalty. In addition the price and quality variable have contribution 40,91%, and the remaining59,09% is effected by other factors that are not examined in this research.